2008
DOI: 10.1007/s10567-008-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

Parents Who Abuse: What Are They Thinking?

Abstract: Child abuse is a major social concern around the world. Important to tackling the problem is an understanding of the mechanisms contributing to abusive parenting. This article brings together research on the cognitive variables associated with abusive or high-risk parenting. Considered are dysfunctional child-centered and parent-centered cognitions as potentially critical correlates of abusive behavior. The development of dysfunctional cognitions is also explored. Cognitive vulnerabilities alone are typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 60 publications
1
22
0
1
Order By: Relevance
“…This indicates that the presence of more risk factors places a higher demand on the mother‐to‐be, resulting in less mental resources to think about the future child and the upcoming motherhood. These findings are in line with the majority of existing studies indicating that the presence of risk factors negatively affects mothers’ RF ability, with HR women have lower RF and more negative mental representations (Huth‐Bocks et al., ; Leigh, ; Seng & Prinz, ; Theran et al., ). An exception to the rule is a study by Perry et al (), who found similar prenatal RF levels for both HR and LR women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates that the presence of more risk factors places a higher demand on the mother‐to‐be, resulting in less mental resources to think about the future child and the upcoming motherhood. These findings are in line with the majority of existing studies indicating that the presence of risk factors negatively affects mothers’ RF ability, with HR women have lower RF and more negative mental representations (Huth‐Bocks et al., ; Leigh, ; Seng & Prinz, ; Theran et al., ). An exception to the rule is a study by Perry et al (), who found similar prenatal RF levels for both HR and LR women.…”
Section: Discussionsupporting
confidence: 89%
“…Children from an “at‐risk” population generally have higher chances of less favorable developmental outcomes. These risk factors impact child development either directly or indirectly through parenting capacities and parent–child interactions (Cyr, Euser, Bakermans‐Kranenburg, & van IJzendoorn, ; Seng & Prinz, ). Parental RF could potentially be an important target for prevention and intervention programs, as it has been associated with certain established risk factors, parenting behaviors, and child outcomes (Benbassat & Priel, ; Rosenblum et al., ; Sharp & Fonagy, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Seng & Prinz ). In abusive families, there are more negative and less positive interactions between parents and children (Seng & Prinz ), and family conflicts were found to be essential in crisis situations with adolescents having psychiatric problems (e.g. Günter et al .…”
Section: Introductionmentioning
confidence: 99%
“…Discussed are factors that may explain parental maladaptive schema, executive functioning problems, and maladaptive appraisals. Seng & Prinz [13] focused on a broader ecological context. While cognitions may occur at an individual level they are shaped in part by interpersonal, intrapersonal, direct and indirect environmental factors.…”
Section: Introductionmentioning
confidence: 99%